Winter town - Emond, Stephen (Little, Brown, 2011)
Evan and Lucy, childhood best friends who grew apart after years of seeing one another only during Christmas break, begin a romance at age seventeen but his choice to mindlessly follow his father's plans for an Ivy League education rather than becoming the cartoonist he longs to be, and her more destructive choices in the wake of family problems, pull them apart.